The potential for CETP inhibition to reduce cardiovascular disease risk. - Ansell, B; Hobbs, F (2006)
BACKGROUND: Although reductions in cardiovascular risk can be achieved by lowering low-density lipoprotein cholesterol, treated patients remain at substantial risk. Epidemiological studies have established that higher levels of high-density lipoprotein cholesterol (HDL-C) are strongly associated with reduced cardiovascular risk, and therefore raising levels of HDL-C may be beneficial. The activity of cholesteryl ester transfer protein (CETP) appears to be inversely correlated with HDL-C levels and thus CETP is an attractive target for intervention to raise levels of HDL-C and potentially reduce residual cardiovascular risk. OBJECTIVES: This paper reviews the evidence for an atheroprotective role of higher levels of HDL-C, the function of CETP in cholesterol metabolism, and the concept of CETP inhibition as a potential new strategy for decreasing cardiovascular risk. An analysis of clinical studies of CETP inhibition was also performed. METHODS: MEDLINE (1966 to June 2006), EMBASE (1974 to June 2006), and cardiology conference proceedings were searched for clinical trials of CETP inhibition. RESULTS: Thirteen reports involving vaccine-based and pharmacological inhibition of CETP were found. Modest and inconsistent elevation of HDL-C was observed with vaccine-based therapy, whereas HDL-C elevation with pharmacological inhibitors was greater and more consistent. CONCLUSIONS: Elevation of HDL-C via CETP inhibition appears to be a potentially promising approach to reduce cardiovascular disease. Preliminary studies suggest benefits of CETP inhibition on serum lipid levels, and ongoing studies should establish the effects on atherosclerosis and cardiovascular events.